Making rights a reality?: disability rights activists and legal mobilization - Vanhala, Lisa (Cambridge disability law and policy series, 2011)
"Making Rights a Reality? explores the way in which disability activists in the United Kingdom and Canada have transformed their aspirations into legal claims in their quest for equality. It unpacks shifting conceptualizations of the political identity of disability and the role of a rights discourse in these dynamics. In doing so, it delves into the diffusion of disability rights among grassroots organizations and the traditional disability charities. It then shows how the diffusion of this rights model of disability can explain how and why disability activists have deployed legal strategies in pursuit of their goals. The book draws on a wealth of primary sources including court records and campaign documents and encompassing interviews with more than sixty activists and legal experts. While showing that the disability rights movement has had a significant impact on equality jurisprudence in two countries, the book also demonstrates that the act of mobilizing rights can have consequences, both intended and unintended, for social movements themselves"--Provided by publisher